Fosab, but not fosaa, plays important role in learning and memory in fish—insights from zebrafish gene knockout study - Wang, Qiuling; Zhang, Lixin; Zhu, Chenyuan; Lu, Ke; Wu, Jiaqi; Liang, Xu-Fang (Frontiers in Cell and Developmental Biology, 2025)
Introduction: Learning and memory allow individuals to adapt to their environmental needs and survive. Fish have the ability to solve complex learning tasks, associative learning, and flexible spatial memory. The proto-oncogene fos (c-fos) has been reported to be involved in brain development, learning and memory in mammals. However, whether the c-fos plays a vital role in learning and memory in fish is unclear.Methods: Almost all fish have two paralogues of c-fos named fosaa and fosab. We used CRISPR/Cas9 technology to generate fosaa and fosab knockout zebrafish models.Results: In this study, we discovered the brain weight marked reduction in fosaa−/− and fosab−/− zebrafish compared with the wild-type (WT) (AB strain) zebrafish. In the T-maze behavioral assay, the fosab−/− zebrafish took significantly more than the average time to complete the assigned trial as the increase in the days compared to WT zebrafish, while the fosaa−/− zebrafish did not show a notable variance. The average time to complete the trial in fosab−/− zebrafish was significantly higher than in WT zebrafish. The relative mRNA expression level of c-jun in fosab−/− zebrafish was significantly higher than that in WT zebrafish, while the fosaa−/− zebrafish has no discernible trend. Additionally, the phylogenetic and multiple amino acid alignment results indicated that fish fosab has a higher identity with mammals Fos.Discussion: By integrating the above results, we found that fosab, but not fosaa, may possess a learning and memory function in fish. For the first time, we illustrated the role of fosaa and fosab in learning and memory via c-fos knockout in fish, which can provide new insights into environmental adaptation.